A Novel Role for CD4(+) T Cells in the Control of Cachexia() - Wang, Zhuangzhi (J Immunol, 2008)
Cachexia is the dramatic weight loss and muscle atrophy seen in chronic disease states, including autoimmunity, cancer, and infection, and is often associated with lymphopenia. We have previously shown that CD4(+) T cells that express the lowest density of CD44 (CD4(+)CD44(v.low)) are significantly reduced in diabetic NOD mice that are cachexic compared with diabetic mice that are not cachexic. Using this model, and a model of cancer cachexia, we test the hypothesis that CD4(+)CD44(v.low) cells play an active role in protecting the host from cachexia. CD4(+)CD44(v.low) cells, but not CD4(+) cells depleted of CD44(v.low) cells, delay the onset of wasting when infused into either diabetic or prediabetic NOD recipients. However, no significant effect on the severity of diabetes was detected. In a model of cancer cachexia, they significantly reduce muscle atrophy, and inhibit muscle protein loss and DNA loss, even when given after the onset of cachexia. Protection from wasting and muscle atrophy by CD4(+)CD44(v.low) cells is associated with protection from lymphopenia. These data suggest, for the first time, a role for an immune cell subset in protection from cachexia, and further suggest that the mechanism of protection is independent of protection from autoimmunity.